Relationship of Dietary Habits with Obesity in University Students of Lahore: A Cross-Sectional Study - Ramisha Ibtisam, Tayyaba Fatima, Muhammad Imran Hussain, Saira Khalid, Mavra Javed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: There is not sufficient data available on the relationship of dietary habits with obesity in university students ofLahore in Pakistan.The freedom of choice that came from the transition of constricted high school environment to a less regulating environment of the university encourage students towards more detrimental food consumption patterns. Aim: To evaluate the relationship between eating habits and obesity and ascertain its influence on the pervasiveness of obesity in university students. Method: A cross-sectional study was carried out between a sample of 200 undergraduate students, aged 19-22+2 years old, between December 15, 2021 till March 15, 2022, from Riphah International university Lahore Region of Punjab, Pakistan. Students handed over a previously tested closed-ended (static) questionnaire encompassingdemographics (age, semester etc.), dietary patternsincludingthe frequency of their consumption of food groups and anthropometric measurements of themselves. Convenience sampling was used to select the partaker. Results: The pervasiveness of obesity 34.44%(38.89% overweight) was soaring high between partakers. It was notable that Body Mass Index (BMI) and the food habits of university students concerning junk food were interconnected. Almost all the partakers were oblivious that many metabolic, respiratory and lower GIT syndromes have obesity as their prominent risk factor. Students skipping two major meals regularly were not few (71.1%). Those who have fried (45.6%) and bakery foods (74.4%) daily were also quite large in numbers. Skipping breakfast and enjoying 3 or more snacks amidst major meals was a norm directly interlinked with obesity after managing for confounding factors.The pervasiveness of obesity was equitably elevated in our sample population and seems to be influenced by various elements associated to student’s dietary patterns. This necessitates for periodic conscientious health education interventions on balanced dietary patterns and healthy lifestyle. Conclusion: This study intends to evaluate the relationship between eating habits and obesity and ascertain its influence on the pervasiveness of obesity in university students. Qualitative studies are required to pinpoint determinants of unhealthy dietary patterns in university students. Keywords: Dietary habits; obesity; BMI; Food Consumption pattern; university students; cross-sectional survey;